Methods of learning the main alpine-skiing techniques taught in romanian sports universities - Ene-Voiculescu, C.; Ene-Voiculescu, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The advancement of the techniques and technical methods of teaching alpine skiing represents the primary goal of the theoretical and practical field of skiing (Fekete J., Trifa l., Mateas C., 2002; Balint Ghe., 2005; Ene-Voiculescu C, 2006). Sports universities include as a component in their curriculum for the first year of study (applied to 75 subjects), the Mountain Sports discipline. In this discipline, Alpine Skiing has a Programme of study consisting of 14 hours of theoretical courses and 56 hours of practical courses. This program will be taught during the Winter in the skiing resort of Predeal, in the Carpathian Mountains at an altitude of 700m.